Molecules vs. morphology in avian evolution: the case of the "pelecaniform" birds. - Hedges, S B (1994)
The traditional avian Order Pelecaniformes is composed of birds with all four toes connected by a web. This "totipalmate" condition is found in ca. 66 living species: 8 pelicans (Pelecanus), 9 boobies and gannets (Sula, Papasula, Morus), ca. 37 cormorants (Phalacrocorax), 4 anhingas or darters (Anhinga), 5 frigatebirds (Fregata), and 3 tropicbirds (Phaethon). Several additional characters are shared by these genera, and their monophyly has been assumed since the beginning of modern zoological nomenclature. Most ornithologists classify these genera as an order, although tropicbirds have been viewed as related to terns, and frigatebirds as relatives of the petrels and albatrosses. DNA.DNA hybridization data indicated that the pelicans are most closely related to the Shoebill (Balaeniceps rex), a stork-like bird that lives in the swamps of central Africa; the boobies, gannets, cormorants, and anhingas form a closely related cluster; the tropicbirds are not closely related to the other taxa; and the frigatebirds are closest to the penguins, loons, petrels, shearwaters, and albatrosses (Procellarioidea). Most of these results are corroborated by DNA sequences of the 12S and 16S rRNA mitochondrial genes, and they provide another example of incongruence between classifications derived from morphological versus genetic traits.